PENGEMBANGAN KETERAMPILAN DAN KAPASITAS UMKM SEBAGAI KUNCI KESUKSESAN JANGKA PANJANG STUDI KASUS UMKM di KECAMATAN BALIGE - Siallagan, Dahlia Nopelina; Simangunsong, Herlina; Handayani, Rina (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2024)
This study aims to determine the development of skills and capacities in Micro, Small and Medium Enterprises (MSMEs) and identify the factors that influence the long-term success of MSMEs in Balige District, Toba Regency. MSMEs have an important role in the local and national economy, therefore upgrading their skills and capacities is the key to achieving sustainable growth. The research methods used are surveys, interviews, and secondary data analysis. The research sample consisted of various types of MSMEs in Balige District, Toba Regency. The research results show that developing the skills and capacity of MSMEs has a positive impact on their business performance. Managerial, financial, marketing and technical skills are key factors that influence the ability of MSMEs to compete in the market. In addition, external factors such as access to finance, government support, and infrastructure also play an important role in the long-term success of MSMEs. Regional government support in the form of training, market access and infrastructure are important factors in increasing the competitiveness of MSMEs. This research provides a better understanding of the importance of skills and capacity development in enhancing the long-term success of MSMEs. The implications of this research are the government and related stakeholders in efforts to increase the skills and capacity of MSMEs and provide adequate support to create a conducive environment for the growth of MSMEs in Balige District, Toba Regency. This will contribute to the development of the local economy and the welfare of local communities. Keywords: MSMEs; Skills Development; MSME capacity